A Dynamic Spectrum Access Strategy Based on Real-Time Usability in Cognitive Radio Sensor Networks - Zemin Hu; Yongmei Sun; Yuefeng Ji (2011 Seventh International Conference on Mobile Ad-hoc and Sensor Networks, 2011)
Currently, Wireless Sensor Networks (WSN) mostly operate on the fixed and unlicensed Industrial, Scientific and Medical (ISM) spectrum. With the increasing spectrum shortage in WSN, the Cognitive Radio Sensor Networks (CRSN) is proposed to employ the Cognitive Radio (CR) technology to utilize the spectrum resources dynamically (i.e., Dynamic Spectrum Access, DSA). However, it's a challenge to increase the delivery rate and the throughput in the CRSN because of the power and process restrictions. In this paper, with the consideration of the spectrum idle condition and communication capability, a novel DSA strategy based on the Real-time Usability (DSARU) is presented. And the energy-saving updating algorithm of the spectrum real-time usability is proposed to sense the spectrum changes. Based on the IEEE 802.15.4, DSARU simulation model and experiment system are set up to evaluate the transmission performances. Both simulation and experiment results demonstrate that the DSARU strategy can efficiently increase the delivery rate and throughput, especially under the condition of spectrum interference.